The effects of temperature and donor piglet age on the transcriptomic profile and energy metabolism of myoblasts - Metzger, Katharina; Kalbe, Claudia; Siengdee, Puntita; Ponsuksili, Siriluck (Frontiers in Physiology, 2022)
Rapid climate change is associated with frequent extreme heat events and the resulting thermal stress has consequences for the health, welfare, and growth of farm animals. The aim of this study was to characterize the transcriptional changes and the effects on energy metabolism in proliferating porcine myoblasts derived from piglets of different ages, representing differences in thermoregulatory abilities, and cultivated below (35°C) and above (39°C, 41°C) the standard cultivation temperature (37°C). Satellite cells originating from Musculus rhomboideus of piglets isolated on days 5 (P5, thermolabile) and 20 (P20, thermostable) of age were used. Our expression analyses highlighted differentially expressed genes in porcine myoblasts cultures under heat or cold induced stress. These gene sets showed enrichment for biological processes and pathways related to organelle fission, cell cycle, chromosome organization, and DNA replication. Culture at 35°C resulted in increased metabolic flux as well as a greater abundance of transcripts of the cold shock protein-encoding gene RBM3 and those of genes related to biological processes and signaling pathways, especially those involving the immune system (cytokine–cytokine receptor interaction, TNF and IL-17 signaling pathways). For cultivation at 39°C, differences in the expression of genes related to DNA replication and cell growth were identified. The highest glutathione index ratio was also found under 39°C. Meanwhile, cultivation at 41°C induced a heat stress response, including the upregulation of HSP70 expression and the downregulation of many biological processes and signaling pathways related to proliferative ability. Our analysis also identified differentially expressed genes between cells of donors with a not yet (P5) and already fully developed (P20) capacity for thermoregulation at different cultivation temperatures. When comparing P5 and P20, most of the changes in gene expression were detected at 37°C. At this optimal temperature, muscle cells can develop to their full capacity. Therefore, the most diverse molecular signaling pathways, including PI3K-Akt signaling, Wnt signaling, and EGFR tyrosine kinase inhibitor, were found and are more pronounced in muscle cells from 20-day-old piglets. These results contribute to a better understanding of the mechanisms underlying the adaptation of skeletal muscle cells to temperature stress in terms of their thermoregulatory ability.